Synthesis and evaluation of some substituted 1,3,4-thiadiazole derivatives - (:unkn) unknown (My University, 1995)
5-[p-(acetylamino)phenyl]-2-substitutedamino-1,3,4-thiadiazole derivatives were prepared by the cyclisation reaction of sulphuric acid on 1-[p-(aminoacetyl)phenyl]-4-alkyl/arylthiosemicarbazides. The intermediate thio semicarbazides were formed by the condensation of p-(acetylamino)benzoylhydrazine with corresponding isothiocyanates. The structures of the compounds were elucidated by use of their IR, 1H NMR and mass spectral data.
Keywords: 1,3,4-thiadiazoles; thiosemicarbazides